Photoperiod Control of Plant Growth: Flowering Time Genes Beyond Flowering - Osnato, Michela; Cota, Ignacio; Nebhnani, Poonam; Cereijo, Unai; Pelaz, Soraya (Frontiers in Plant Science, 2022)
Fluctuations in environmental conditions greatly influence life on earth. Plants, as sessile organisms, have developed molecular mechanisms to adapt their development to changes in daylength, or photoperiod. One of the first plant features that comes to mind as affected by the duration of the day is flowering time; we all bring up a clear image of spring blossom. However, for many plants flowering happens at other times of the year, and many other de-velopmental aspects are also affected by changes in daylength, which range from hypocotyl elongation in Arabidopsis to tuberization in potato or autumn growth cessation in trees. Strik-ingly, many of the processes affected by photoperiod employ similar gene networks to re-spond to changes in the length of light/dark cycles. In this review, we have focused on devel-opmental processes affected by photoperiod that share similar genes and gene regulatory net-works.